2022
DOI: 10.1186/s40104-022-00679-2
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of 3D genome architecture across wild boar and Bama pig adipose tissues

Abstract: Background A growing body of evidence has revealed that the mammalian genome is organized into hierarchical layers that are closely correlated with and may even be causally linked with variations in gene expression. Recent studies have characterized chromatin organization in various porcine tissues and cell types and compared them among species and during the early development of pigs. However, how chromatin organization differs among pig breeds is poorly understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…In this study, we generated 11 in situ Hi-C libraries ( Table S1 ) using the same experimental protocols as the Hi-C dataset that we previously reported ( 87 ). Briefly, 1 g of ATs were cross-linked with a final concentration of 4% freshly prepared formaldehyde (Sigma Aldrich) for 30 min at room temperature, followed by quenching with glycine (Amresco) at a final concentration of 0.25 mol l −1 .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we generated 11 in situ Hi-C libraries ( Table S1 ) using the same experimental protocols as the Hi-C dataset that we previously reported ( 87 ). Briefly, 1 g of ATs were cross-linked with a final concentration of 4% freshly prepared formaldehyde (Sigma Aldrich) for 30 min at room temperature, followed by quenching with glycine (Amresco) at a final concentration of 0.25 mol l −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The main emerging challenges for understanding the molecular mechanisms of specific expression patterns is to identify the transcriptional regulatory elements at a genome‐wide scale. Recently, the chromatin 3D genome architecture of porcine has been investigated in porcine LDM (Yuan et al, 2021) and adipose tissues (Zhang et al, 2022), using the Hi‐C method. The results indicate that A/B compartments and topologically associating domains are relatively stable and conserved in different pig breeds or embryonic development stages, but the promoter enhancer interactions are more dynamic and widespread.…”
Section: Functional Annotation Of Genetic Elementsmentioning
confidence: 99%
“…Studies have revealed that changes in 3D chromatin structure during growth and development, as well as long-range interactions within speci c breeds or tissues, play regulatory roles in gene expression [20]. In a comparison of Bama pigs and wild boar, chromatin architecture contributes to determining the regulatory mechanism of phenotypic differences between Bama pigs and wild boar [21]. Furthermore, the chromatin architecture had contributed to the analyses of pig phenotypes [9,22].…”
Section: Introductionmentioning
confidence: 99%